Regional Financial Management Policies and Their Implications for Regional Governance - Arrazak, Muhammad Afdhal; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to understand the role of regional financial management policies and their implications for regional governance. This study uses a literature review method by examining various scientific articles discussing regional financial policies, budget management, and governance practices. The results of the discussion indicate that regional financial management policies not only function as technical guidelines for budget management but also as an important instrument in building orderly and directed governance. The quality of budget planning, flexible yet controlled implementation, and effective oversight are key factors influencing the accountability and efficiency of regional financial management. Furthermore, consistent policy implementation encourages transparency and strengthens the institutional capacity of regional governments, despite the challenges of differences in resource capabilities and regional fiscal conditions. Overall, regional financial management policies play a strategic role in strengthening regional governance and supporting public interest-oriented governance.